(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2025)
This study aims to know the importance of thoughts in the process of civilizational construction at Malek Bennabi, who gave the problem of civilization in the Islamic community great attention in his studies and research, in which he concluded that the thoughts held by man are the source and the basis of the entire cultural problem. Malek Bennabi concluded that the problem of civilization is solved only by solving three problems: the problem of man, the problem of soil and the problem of time. He laid down three basic stages in the Islamic civilization construction, indicating the importance of thoughts in these stages: the stage of spirit, the stage of mind and the stage of instinct. Keywords: Civilization,Thoughts, Civilizational construction.